Eye trematode infection in small passerines in Peru caused by Philophthalmus lucipetus, an agent with a zoonotic potential spread by an invasive freshwater snail - Literák, Ivan; Heneberg, Petr; Sitko, Jiljí; Wetzel, Eric J; Cardenas Callirgos, Jorge Manuel; Čapek, Miroslav; Valle Basto, Daniel; Papoušek, Ivo (Parasitology international, 2013)
Until now, four species of eye trematodes have been found in South America. Of them, Philophthalmus lucipetus (synonymized with Philophthalmus gralli) displays a broad host spectrum, with at least 30 bird species (prevalently large water birds), five mammal species and humans serving as definitive hosts, and with snails Fagotia (Microcolpia) acicularis, Amphimelania holandri, Melanopsis praemorsa and Melanoides tuberculata serving as intermediate hosts. When examining a total of 50 birds of ten species in the wetland of Pantanos de Villa, Lima, Peru in July 2011, eye trematodes were identified visually in the edematous conjunctival sac of 11 (48%) out of 23 resident many-colored rush tyrants Tachuris rubrigastra. Based on morphometric characteristics, the trematodes were identified as P. lucipetus. ITS2 and CO1 gene of the examined specimens combined showed a 99% similarity to an Iranian isolate of Philophthalmus sp. from the intermediate host Melanoides tuberculata, an invasive freshwater snail, suggesting that these two isolates represent the same species with a wide geographical range. Moreover, the prevalence of infection with the philophthalmid cercariae was 31% in 744 Melanoides tuberculata examined in Pantanos de Villa in 2010. It is evident that P. lucipetus occurs throughout the world as well as locally, including Eurasia and South America. Here we report this trematode for the first time in Peru, and we were the first to sequence any of the South American eye trematodes. Low host specificity of P. lucipetus and the invasive character of Melanoides tuberculata as a competent intermediate host suggest that eye trematodosis caused by P. lucipetus may emerge frequently in various parts of the world, especially in the tropics. Increase of the zoonotic potential of the P. lucipetus associated with this invasive snail spreading across the world is predictable and should be of interest for further research.
Keywords: Animals; Base Sequence; ribozomální DNA; DNA, Ribosomal; infekce červy třídy Trematoda; Trematode Infections; DNA, Mitochondrial; Disease Vectors; Passeriformes; Echinostomatidae; Molecular Sequence Data; nemoci ptáků; Eye Infections, Parasitic; Bird Diseases; molekulární sekvence - údaje; Sequence Alignment; mitochondriální DNA; sekvence nukleotidů; Sequence Analysis, DNA; infekce přenášené vektorem; oční infekce parazitární; Snails; zvířata; sekvenční analýza DNA; Peru; hlemýždi; sekvenční seřazení